Exploring the ElectroRetinoGraphy as a biomarker for predicting and monitoring therapeutic response to antidepressants in major depressive disorder: study protocol for the MESANTIDEP trial - de Deus, Marie; Petit, Charlotte; Moulard, Marie; Cosker, Eve; Mellouki Bendimred, Naoual; Albuisson, Éliane; Maruani, Julia; Geoffroy, Pierre-Alexis; Schwitzer, Thomas (Frontiers in Psychiatry, 2025)
BackgroundMajor depressive disorder (MDD) is a frequent and highly debilitating condition for which current antidepressant treatments show limited effectiveness. In addition, their implementation requires one or more trial-and-error processes, which involves months of untreated illness. Achieving faster efficacy by identifying the most adapted treatment for each patient as the first line treatment could significantly reduce MDD-related morbidity and mortality while enhancing patients’ quality of life. To achieve this goal, there is a need to identify markers for predicting and monitoring therapeutic response to antidepressants.MethodsThe MESANTIDEP study is designed to identify electroretinographic (ERG) biomarkers that can predict the therapeutic response at 12 weeks to the two main classes of antidepressants prescribed as first-line treatments for MDD: Selective Serotonin Reuptake Inhibitors (SSRIs) and alpha-2 adrenergic receptor antagonists (α2-antagonists). Secondly, the study aims to explore the relationship between ERG measurements and therapeutic response at 6 and 12 weeks in MDD patients treated with SSRIs or α2-antagonists. To this end, patients diagnosed with MDD and needing to start an antidepressant from the SSRI or α2-antagonist classes will be enrolled. At the inclusion visit, prior to starting their antidepressant treatment, patients will undergo various assessments, including clinical and sleep questionnaires, as well as ERG tests. Patients will initiate their antidepressant treatment the day after the inclusion visit. Subsequent evaluations, identical to those at baseline, will be conducted 6 and 12 weeks afterwards to monitor therapeutic response to antidepressants.DiscussionThe MESANTIDEP study will contribute to identify ERG markers predicting and monitoring the therapeutic response to antidepressants. If such markers are highlighted, it is intended to help clinicians in the treatment management of MDD patients. ERG measurements being easy to perform and accessible to all, they could be integrated into a multimodal treatment approach in routine clinical practice. It would enable more rapid therapeutic intervention tailored to each patient could reduce the functional impact of the disease, improve patients’ quality of life, and decrease MDD-associated morbidity and mortality.Clinical Trial RegistrationClinicaltrials.gov, identifier NCT06532604.